1976
DOI: 10.1002/mpo.2950020102
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear cell content of human solid tumors

Abstract: The mononuclear cell content and mononuclear cell function of human solid tumors were determined. Twenty-eight primary, and 17 metastatic solid tumors, including 6 lymph node metastases, were obtained from 45 patients. Cells were released from the tumors by mincing, scraping, and sieving. Analysis of the cellular content was determined by light microscopy, and tumor lymphocyte function was determined by stimulation of blastogenesis with PHA, PWM, Con-A, MLC, and SLO. A median of 3.3 X 10(7) tumor cells with 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…During the past two decades numerous studies have revealed interactions between malignant cells and the stroma that promote diverse tumor functions including angiogenesis 4,5 , metastasis 6 , and immunosuppression 7,8 . Stromal cells differ between patients and tumor types [9][10][11][12][13][14][15] and the abundance of certain stromal cell populations are used in the clinic as biomarkers [16][17][18][19] and therapeutic targets [20][21][22][23][24][25] . These studies motivate direct measurements of cell types and the interactions between them in human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades numerous studies have revealed interactions between malignant cells and the stroma that promote diverse tumor functions including angiogenesis 4,5 , metastasis 6 , and immunosuppression 7,8 . Stromal cells differ between patients and tumor types [9][10][11][12][13][14][15] and the abundance of certain stromal cell populations are used in the clinic as biomarkers [16][17][18][19] and therapeutic targets [20][21][22][23][24][25] . These studies motivate direct measurements of cell types and the interactions between them in human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the early studies on the immune microenvironment of cancer focused on the characterization and functions of cellular and humoral immune components in the tumor microenvironment [1136] These studies established that immunocytes including T cells [23, 32], B cells [14, 17], NK cells [24, 31] and macrophages [19, 20, 26, 27, 29, 33, 35, 36] have the capacity to infiltrate solid tumors in humans and in animals. Other studies demonstrated that immunoglobulins (Ig) and complement components could be detected in the microenvironment of solid tumors.…”
Section: From Infancy To Young Adulthoodmentioning
confidence: 99%
“…It was demonstrated that inflammatory cells (mainly macrophages) as well as proinflammatory molecules such as cytokines and chemokines whose physiologic function is to constitute a firewall against infectious agents, are causally involved in the initiation of certain types of cancer (inflammation-linked cancers) or in tumor progression of essentially all types of cancer [69, 70]. As mentioned above, several studies from the seventies of last century reported that mononuclear cells infiltrate solid tumors [19, 20, 26, 27, 29, 33, 35, 36]. It took several years to establish that such cells are heavily involved in the pro malignancy functions of cancer-linked inflammation [6972].…”
Section: From Infancy To Young Adulthoodmentioning
confidence: 99%